ANALISIS FSKTOR-FAKTOR PENENTU NIAT MENGGUNAKAN APLIKASI HALODOC - Triana Wardhatun Jannah; Didik Setyawan; Sugiyarmasto . (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the effect of the attitude variable on the intention to use the Halodoc application. The intention to use Halodoc application is caused by the attitudes and trusts toward using the Halodoc application. Attitudes and trusts have an impact on the intention to us Halodoc application The data was obtained through questionnaires which distributed to the general public, both those who have used or have not used the Halodoc application. The sample which used in this study was 200. The sampling technique used was purpose sampling. Hypothesis testing is done by using SEM (Structural Equation Modeling) analysis with the path analysis method. The results of this study indicate that five hypotheses are supported and three hypotheses are not supported. The relationship between attitudes and trusts has a positive effect on the intention to use the Halododc application. The variable of vulnerability has an effect on attitudes, vulnerability has no effect on t rust. The risk variable has no effect on attitudes and trusts. Characteristics of the application have a positive effect on attitudes and tr usts.